Psychological Well-Being as a Predictor of Academic Resilience Ahead of Vocational Competency Exams - Nuria Audrin Melani; Rima Wilantika (TAUJIHAT: Jurnal Bimbingan Konseling Islam, 2025)
Vocational secondary schools play an important role in preparing students for the world of work. However, high academic demands often cause stress, especially in the run-up to vocational competency exams. The main objective of this study is to know the relationship between psychological well-being and academic resilience in vocational secondary school students in the run-up to their final exams. The research method used quantitative correlational analysis. A total of 190 Year 12 students at a vocational school in Lampung were selected as research subjects through cluster random sampling. The instruments used included an academic resilience scale and a psychological well-being scale. Data analysis used Pearson's Product-Moment correlation with the help of SPSS version 25.0 software. The results showed a highly significant positive relationship between psychological well-being and academic resilience (r = 0.675 and p = 0.000). Psychological well-being accounted for 45.6% to students' academic resilience. These findings reinforce the role of psychological well-being as an important predictor of academic resilience in vocational education. The implication is that interventions to improve psychological well-being in vocational schools are necessary to prepare students better to face exam pressure and academic challenges leading up to exams.